2006
DOI: 10.1110/ps.052055206
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric and structural studies of the nitric oxide carrier S‐nitrosoglutathione bound to human glutathione transferase P1‐1

Abstract: The nitric oxide molecule (NO) is involved in many important physiological processes and seems to be stabilized by reduced thiol species, such as S-nitrosoglutathione (GSNO). GSNO binds strongly to glutathione transferases, a major superfamily of detoxifying enzymes. We have determined the crystal structure of GSNO bound to dimeric human glutathione transferase P1-1 (hGSTP1-1) at 1.4 Å resolution. The GSNO ligand binds in the active site with the nitrosyl moiety involved in multiple interactions with the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 55 publications
4
29
1
Order By: Relevance
“…Albumin also contains a redox-active Cys residue which is normally about 50% present as the S-cysteinyl disulfide form. This thiol has been suggested to function as a carrier of NO and also to function in detoxification [146,147]. The content of this disulfide was also found to correlate with the plasma Cys/CySS redox potential [138].…”
Section: Cys/cyss Couple Is the Major Low Molecular Weight Thiol/disumentioning
confidence: 94%
“…Albumin also contains a redox-active Cys residue which is normally about 50% present as the S-cysteinyl disulfide form. This thiol has been suggested to function as a carrier of NO and also to function in detoxification [146,147]. The content of this disulfide was also found to correlate with the plasma Cys/CySS redox potential [138].…”
Section: Cys/cyss Couple Is the Major Low Molecular Weight Thiol/disumentioning
confidence: 94%
“…The experimental conditions and data analysis were similar to those described elsewhere (Té llez-Sanz et al, 2006;Quesada-Soriano et al, 2009). The binding of active site ligands to the C47S/Y108V GST P1-1 mutant quenches the intrinsic fluorescence of the enzyme as was described for wt GST P1-1 Ortiz-Salmeró n et al, 2003;Caccuri et al, 1991).…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…The sample preparation and ITC experiments were carried out as previously described elsewhere (Té llez-Sanz et al, 2006;Quesada-Soriano et al, 2009). Titrations were routinely performed in 20 mM sodium phosphate, 5 mM NaCl, 0.1 mM EDTA at pH 7.…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 99%
“…Recently, the crystal structure of S-nitrosoglutathione bound to hGSTP1-1 showed that the S-nitrosoglutathione ligand binds in the active site with the nitrosyl moiety involved in multiple interactions with the enzyme. 23 The crystallographic analysis also revealed three possible conformations of the nitroso group, which could be modeled with ~33% occupancy for each. In one conformation the nitrosyl moiety was stabilized by water-mediated interactions with Arg13 and Tyr108.…”
Section: Resultsmentioning
confidence: 97%